Pharmacodynamics of Glyburide, Metformin, and Glyburide/Metformin Combination Therapy in the Treatment of Gestational Diabetes Mellitus. Issue 6 (25th January 2020) - Shuster, Diana L.; Shireman, Laura M.; Ma, Xiaosu; Shen, Danny D.; Flood Nichols, Shannon K.; Ahmed, Mahmoud S.; Clark, Shannon; Caritis, Steve; Venkataramanan, Raman; Haas, David M.; Quinney, Sara K.; Haneline, Laura S.; et al.
Abstract : In gestational diabetes mellitus (GDM), women are unable to compensate for the increased insulin resistance during pregnancy. Data are limited regarding the pharmacodynamic effects of metformin and glyburide during pregnancy. This study characterized insulin sensitivity (SI), β‐cell responsivity, and disposition index (DI) in women with GDM utilizing a mixed‐meal tolerance test (MMTT) before and during treatment with glyburide monotherapy (GLY, n = 38), metformin monotherapy (MET, n = 34), or GLY and MET combination therapy (COMBO; n = 36). GLY significantly decreased dynamic β‐cell responsivity (31%). MET and COMBO significantly increased SI (121% and 83%, respectively). Whereas GLY, MET, and COMBO improved DI, metformin (MET and COMBO) demonstrated a larger increase in DI ( P = 0.05) and a larger decrease in MMTT peak glucose concentrations ( P = 0.03) than subjects taking only GLY. Maximizing SI with MET followed by increasing β‐cell responsivity with GLY or supplementing with insulin might be a more optimal strategy for GDM management than monotherapy.